Enhancing the supply chain management performance using information technology: Some evidence from UAE companies - Sundarakani, B.; Tan, Wee Kwan; Van Over, D. (Inderscience Publishers, 2012)
The objective of this paper is to investigate Supply Chain Management (SCM) performance of selected companies in the United Arab Emirates (UAE) countries upon successful implementation of Information Technology (IT) applications. By carrying out an in-depth qualitative analysis, the paper seeks to evaluate how IT can enhance the SCM performance from a practitioner perspective. The survey results have indicated that respondents are aware that adopting IT does not necessarily translate to immediate benefits. Companies in UAE will, therefore, need to 'educate' their senior managers on using IT systems to streamline their supply chain operations, reduce cycle time and improve supply chain visibility. While most respondents have implemented IT systems for transactional processing, more can be done to implement more advanced IT systems for better planning and decision-making. © 2012 Inderscience Enterprises Ltd.